The Wichita Teacher Inquiry Group (WTIG) Lessening Structural, Cultural, Indirect and Direct Forms of through Cultural Competence and Transformative Teaching and Learning - Linda F. Rhone; Kimberly Johnson Burkhalter (The Advocate, 2012)
Bullying at school is an international phenomenon, and as a result there is a need for teachers to understand bullying behavior at its roots and beyond direct (hitting, kicking, choking) and indirect (gossiping, cyberbullying, silencing one’s voice) forms. If we are really going to lessen bullying at school overtime, we must talk about the unmentionable: Bullying at school is larger than one child pushing, hitting or kicking another. Literature suggests it is quite disappointing that to date there has been no significant impact on bullying at school in the United States (Juvonen, Graham, & Schuster, 2003; Berger, 2007). Literature also suggests there is little to no national conversation about how direct and indirect forms of bullying at school are connected to ideological beliefs, structural practices and cultural competence. This particular study explored the scholarly literature and educational practices of social justice guru, Paulo Freire and their implications for examining ideology, structural practices, cultural competence, and oppression, namely bullying at school. The teacher-participants in this study became known as the Wichita Teacher Inquiry Group. The six 5th grade teachers, diverse in race, gender and experience, were nominated by their principals to be a part of this year-long endeavor. Fifth grade was selected because bullying behavior is most extensive at the middle school level (Archer & Cote, 2005; Eslea & Rees, 2001; Espelage, Meban, & Swearer, 2004; Pellgegrini & Long, 2002). One of the goals of this study was to help 5th grade students learn an appropriate use of power before they transition to middle school. The principals used social justice oriented teaching as the criteria for nominating a teacher. Social justice teachers’ teaching practices are designed to pose thought-provoking problems for students to devise understandings for discussion. They address “key social justice issues locally and globally - regarding racism, class inequality, gender inequalities, planetary pollution and global warming, war and peace, etc., and seek to integrate such issues as themes into the disciplinary subject matters at hand rather than delivering free-standing lectures on them” (Shor, 2011, p. 1.). The nominated teachers who became the six teacher-participants responded to four surveys, participated in nine cultural circles (focused discussion), and were videotaped while teaching a lesson in their respective classrooms. The teacher-participants came to understand the connection between ideology, structure, culture and oppression in their school contexts as well as how all four can perpetuate direct and indirect bullying behavior. As a result of their experiences with this study, the teacher-participants were convinced that teaching from a social justice orientation, a Freirean perspective in particular, has the potential to lessen structural, cultural, indirect, and direct forms of bullying, because it poses thought-provoking questions and addresses power and inequities as it relates to race, social class, gender and the like. They were also convinced that teaching from a social justice perspective could help them to guard against becoming teacher bullies. This study was expected to allow those teachers who were very effective at teaching from a social justice orientation to share their teaching practices with those who had less experience. In the end, all social justice teachers, veteran and novice were expected to enhance their skills through this work. Future research should consider further investigation on how ideological beliefs, structural practices and cultural competence can perpetuate direct and indirect forms of bullying so that teacher education programs can address this before preservice teachers earn a license to teach.
Keywords: Research; Bullying; Ideology; Structural practices at school; Cultural Competence; Critical Multicultural Social Justice Education; Cultural Bullying; Structural Bullying